The Spectator, 2001-10-11. Tab Edition - Spectator, Valdosta State University (Valdosta State University, 2001)
The Spectator, October 11, 2001 Tab Edition. Homecoming 2001.
The Spectator: The Unfiltered, Uncensored Voice of the Students
Born digital draft copy. Converted from QuarkXpress format to PDF. Some content may be incomplete, rendered incorrectly, or different from final print editions. Some fonts have been changed. Processed by Dallas Suttles at Valdosta State University Archives and Special Collections, 2016. dasuttles@valdosta.edu.
Keywords: Valdosta State University -- Periodicals